The ambiguity of leadership : a case of leadership or anti-leadership? - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case study examines the relationship between organizational culture and leadership in a Swedish industrial company. The head of a management division, Gustaf, calls a regular quarterly meeting and the case study considers the events of these meetings in order to determine whether Gustaf adopts the style of leadership or anti-leadership.